Developing ERIES Learning Model to Improve Students-Teacher Basic Teaching Skills Through the Implementation of Lesson Study - Eri Sarimanah (STKIP Singkawang, 2018)
This study is aimed at developing ERIES learning model to improve semester V student-teacher’s basic teaching skills in Teaching Learning Strategy lecture in Indonesian Language and Literature Study Program. Through the implementation of Lesson Study, ERIES model was developed by Exploration, Reflection, Interaction, Elaboration, and Summary steps. The method applied in the study is Research and Development and the approach used is qualitative and quantitative. Qualitative data were gained from needs analysis and response to the developed product, while quantitative data were gained from the test of the product and the effectiveness of the model. Research result shows that ERIES learning model is needed by student-teacher. Structurally this model is valid, relevant and fit the principles of learning model development both in its substance and its structure. Based on the try-out result from experimental research, ERIES learning model is effective to improve student-teacher’s basic teaching skills. The achievement is better than non-ERIES learning model.